2022
DOI: 10.1096/fj.202101817rr
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 modulates intestinal smooth muscle cell phenotype and dampens inflammation‐associated intestinal remodeling

Abstract: Stricture formation is a common complication of Crohn's disease (CD), driven by enhanced deposition of extracellular matrix (ECM) and expansion of the intestinal smooth muscle layers. Nuclear receptor subfamily 4 group A member 1 (NR4A1) is an orphan nuclear receptor that exhibits anti‐proliferative effects in smooth muscle cells (SMCs). We hypothesized that NR4A1 regulates intestinal SMC proliferation and muscle thickening in the context of inflammation. Intestinal SMCs isolated from Nr4a1+/+ and Nr4a1−/− lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…A study demonstrated that NR4A1 inhibits inflammation related intestinal fibrous strictures by mediating the intestinal SMCs phenotype. 44 In addition, the function of ECs (regulation of immune cells and angiogenesis) was considered a key element in the pathological mechanism of IBD, which mediates and exacerbates inflammation in intestine. 45,46 Thus, several studies have proposed new strategies to treat IBD by targeting multiple integrins and adhesion molecules expressed on ECs.…”
mentioning
confidence: 99%
“…A study demonstrated that NR4A1 inhibits inflammation related intestinal fibrous strictures by mediating the intestinal SMCs phenotype. 44 In addition, the function of ECs (regulation of immune cells and angiogenesis) was considered a key element in the pathological mechanism of IBD, which mediates and exacerbates inflammation in intestine. 45,46 Thus, several studies have proposed new strategies to treat IBD by targeting multiple integrins and adhesion molecules expressed on ECs.…”
mentioning
confidence: 99%